Analisis Arus Kas Operasi Dalam Mencapai Nilai Perusahaan Yang Optimal Studi Kasus Pada PT Semen Gresik (Persero) Tbk - Puspitasari, Ratih (Jurnal Ilmiah Kesatuan (JIK), 2010)
Cash flow of an operational activity is cash flow obtained from sales, accounts receivable revenue,payment for trade debt, goods purchasing and other costs. Companyâs value is the price that will be paid by purchaser when the company is sold. The goal of this research is to find out how significant the impact of cash flow used by the company will be, to know whether the operational cash flow can increase the companyâs value optimally, and to measure the companyâs value which is reasonable and interested in by market. The procedure of data collecting used by the author is library research and internet browsing. In addition, the author utlizes descriptive study as well, that is collecting data related to the two variable by literature study. The result of this research shows that at PT Semen Gresik Tbk. operational cash flow has significant influence to the companyâs value, that is significance degree as high as 0,000.